Verso la terza legge sull’assistenza psichiatrica in Italia: la negazione della malattia mentale - Dario, Mariopaolo; Del Missier, Giovanni; Piazzi, Andrea; Stocco, Ester; Testa, Luana (Il sogno della farfalla, 2008)
The authors, continuing their reconstruction of the history of psychiatric legislation in Italy featured in two articles published in the last two issues of this journal, propose a reflection on the origins of the law 180/1978, the so-called Basaglia law, outcome of Bruno Orsini’s efforts, a DemoChristian MP. After the partial failure of the 1968 Mariotti law, the most reforming psychiatric organizations convene with the anti-institutional movements with the aim of abrogating Law 36 of 1904, which still regulated the Italian psychiatric sector and the asylums. The event which triggered this off, at the beginning of 1978, is represented by a referendum held by the Radical party that forces the Parliament to quickly pass an abridged law, the 180, that precedes by a few months the setting up of National Health Service which initially contained the psychiatric reform. Making reference to official documents, to the political writings of the time and to the testimonies of some protagonists involved, the authors examine the parliamentary debate that brings to the enactment of the law, the cultural roots underlying it and the state of psychiatry at the time, within a complex and at times dramatic scientific, philosophic and political context. What becomes apparent is how ideologies which differ among themselves, such as Catholicism and Communism, come together in the new culture of 1968 to produce a law mistakenly considered a revolutionary step for psychiatry. Its theoretical basis lies in the “negation of mental health”, and has, as a consequence, the failure to carry out research into the origins and into the cure of psychiatric pathology.